Absorption, metabolism and homeostasis of zinc in animals and human beings (Veterinary Science, 2017)
Zinc is required for numerous essential functions, related with almost 300 metaloenzymes and their role in gene expression regulation, intracellular signaling, biological membranes stability, etc. The aim of this work is to review and to discuss the knowledge generated in the last years concerning with zinc absorption and metabolism in the organism, as well as the different mechanisms involved in the zinc homeostasis.
Keywords: Zinc; Metabolism; Animals